2012
DOI: 10.1111/j.1741-3729.2012.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of School‐Specific Parenting Processes on Academic Achievement in Adolescence and Young Adulthood

Abstract: There is inconsistency in the current literature regarding the association between dimensions of parenting processes and academic achievement for adolescents. Further, few studies have extended such an association into young adulthood. In this study, we examined the effect of three dimensions of parenting processes, including school‐specific involvement, general parental support, and parental expectations, on academic achievement in adolescence and in young adulthood. Using a large, nationally representative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 48 publications
(126 reference statements)
4
39
1
4
Order By: Relevance
“…In their study, Gordon and Cui (2012) found that parents who were more involved seemed consequently to have a better relationship with their children's teachers, to be more likely to intercede in important school matters and to provide guidance and tutoring to their children's academic performance. However, these conclusions did not entirely fit with what the parents of both groups expressed regarding their participation in school.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Gordon and Cui (2012) found that parents who were more involved seemed consequently to have a better relationship with their children's teachers, to be more likely to intercede in important school matters and to provide guidance and tutoring to their children's academic performance. However, these conclusions did not entirely fit with what the parents of both groups expressed regarding their participation in school.…”
Section: Discussionmentioning
confidence: 99%
“…The transition to secondary school is a period with several developmental tasks, involving academic challenges, decision-making processes, regulation of peer socialisation and important vocational decisions (Brkovic, Kerestes, & Levpuscek, 2014;Diogo, 2007;Ginevra, Nota, & Ferrari, 2015), and for an adaptive transition, parents can act as facilitators (Gordon & Cui, 2012;Simpkins et al, 2009) and as protectors (Spera, 2005). In fact, parental behaviours (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may involve fathers discussing school-related events with their adolescent, and assisting with the completion of homework assignments. School-specific involvement has been linked directly to academic success among youth (Gordon and Cui 2012;Jeynes 2007). For example, Tan and Goldberg (2008) found that, after controlling for mother's involvement, father's involvement in their child's schooling was positively associated with academic achievement among a sample of elementary school children, in grades kindergarten through sixth.…”
Section: Introductionmentioning
confidence: 97%
“…Father's school-related involvement however, is characteristically different from general parental involvement (Gordon and Cui 2012). Rather than being involved in varying aspects of their adolescent's lives, father's schoolrelated involvement encompasses strategic efforts on the part of the father to help their adolescent navigate their way successfully through school-specific work.…”
Section: Introductionmentioning
confidence: 98%